From Signals to Action: Enhancing Respiratory Disease Surveillance with Event-Based Methods: An Expert Opinion - Daoud, Leen; Al Awaidy, Dr. Salah; Ghosn, Nada; Sadek, Mahmoud (International Journal of Innovative Research in Medical Science, 2025)
The workshop From Signals to Action: Enhancing Respiratory Disease Surveillance with Event-Based Methods examined the integration of Event-Based Surveillance (EBS) into national respiratory disease surveillance systems. Experts and participants explored EBS’s role in detecting early signals of outbreaks from non-traditional sources like social media, news, and community networks, complementing Indicator-Based Surveillance (IBS). Key presentations showcased successful case studies from Oman and Lebanon, emphasizing the importance of cross-sectoral collaboration and the integration of human, animal, and environmental health surveillance. Discussions highlighted the challenges of data standardization, verification, and ensuring timely response Tools like the World Health Organization’s Epidemic Intelligence from Open Sources (EIOS) were emphasized as valuable for the media scanning component of Event-Based Surveillance (EBS), utilizing a multi-hazard approach to detect signals from diverse information sources. The tool’s effectiveness was exemplified during mass gatherings, where it supported real-time data collection and analysis to identify potential public health threats. Participants from conflict-affected countries, including Sudan shared how EBS had been crucial in maintaining surveillance when formal systems collapsed. The workshop highlighted the importance of political commitment, sustainable funding, and capacity building to sustain EBS systems. Future challenges like staff turnover and the need for simple, accessible reporting systems in low-resource settings were discussed. Overall, the session stressed that EBS is essential for early detection of public health threats and should be fully integrated into national and regional surveillance frameworks to strengthen health system resilience.